Does providing inmates with education improve postrelease outcomes? A meta-analysis of correctional education programs in the United States - Bozick, Robert (Journal of experimental criminology, 2018)
Our study addresses the question: Does providing inmates with education while incarcerated reduce their chances of recidivism and improve their postrelease employment prospects?